Real-Time Wetting Area Measurement of Micro- and Nanostructured Surfaces with an Acoustic Wave Device - Chiniforooshan Esfahani, Ilia (Langmuir : the ACS journal of surfaces and colloids, 2025)
Wetting characterization on textured surfaces is essential for applications such as improving fluid dynamics in microfluidic devices, enhancing antifouling coatings in maritime environments, and optimizing ink deposition in printing processes. Common methods, including contact angle measurement and optical microscopic imaging methods, often fail to provide in situ, real-time characterization of the interface between liquid and a textured surface. This work studies the wetting of micro- and nanopillar surfaces with an acoustic wave device, quartz crystal microbalance (QCM), which is capable of capturing the real-time partial wetting and transition from Cassie to Wenzel states. The frequency response of the micropillar QCM device was found to have a linear correlation with the area of liquid penetration on the substrate with a limit of detection (LOD) of 0.3% area coverage. Furthermore, the real-time wetting characterization capabilities of the QCM device were validated through experiments involving BSA (bovine serum albumin) adsorption on micropillar-coated surfaces. The device can detect the dynamic wetted behavior of the surface due to protein adsorption. In addition, measurement of the wetting on the nanopillar surface with QCM was demonstrated. The developed method offers a promising solution for the real-time characterization of the penetrated area on the surface, enhancing the interaction between liquids and surfaces in applications such as microfluidic systems, coating technologies, and biomedical devices